Employee Competencies for Business Process Management - Eicker, Stefan; Kochbeck, Jessica; Schuler, Peter M. (Proceedings of 11th International Conference on Business Information Systems (BIS 2008), 2008)
Business process management (BPM) is an approach which empowers companies to react flexibly to new market situations. The main goal of BPM is to improve efficiency and effectiveness of value-adding business processes. The changes caused by globalization do not only concern organization, technologies and processes, but also people. Employee competencies can be crucial competitive advantages. The need for new specialized and competent personnel in BPM becomes apparent from the definition of new roles, such as “Chief Process Officer” (CPO). Field reports and surveys reveal that role concepts of BPM have so far not been completely established, due to a lack of appropriate structures or dueto resistance within the companies. This article considers and analyzes the success factor employee competencies in matters of the implementation of BPM in companies. For this purpose, competencies which are necessary for the roles in BPM are identified.  Moreover, a classification method for the definition of role profiles is developed.
Keywords: Business Process Management; Measurement; Inter-Organizational Processes; Human Factors.